An English Listening Material Development of Listening Materials Production for University Students - Maria Safriyanti (English Study Program University of Pasir Pengaraian, 2021)
This research was designed to develop appropriate listening materials based on the students’ needs of the English Department of Universitas Riau. The Research and Development (R&D) design was applied in this research. The research object was the listening materials development for the first semester students (freshmen) who took listening comprehension class. The researcher did the research started from analyzing the students’ needs, then collecting and choosing the authentic materials based on some resources and lastly developing the materials and the materials were validated by the experts. The product is in the form of collected listening materials and compact disc recorded materials. The criteria of validating materials were based on the existing syllabus and the criteria such as language, length, content, and style of delivery, delivery speed, suitability with curriculum, practicality, clarity of recording, level of difficulty, attractiveness, and effectiveness. The result of validation showed that the listening materials are valid. It can be concluded that materials can be used for the learning activities.